Admission Hyperglycemia Association with Complications in Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease - حجازية مالك; سلمان ربا; سليمان عبير (Latakia University Journal -Medical Sciences Series, 2021)
Introduction: The indicators that assessing the development of an Acute Exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD) should be simple, and correctable such as admission hyperglycemia, which studies have shown its relationship to poor prognosis for many acute diseases like septic shock and acute myocardial infarction. Aims: The primary objective was to study the association between admission hyperglycemia and complications (death, length of hospitalization) in patients with AECOPD and the secondary objective was to study the relationship of admission hyperglycemia with other complications during hospitalization. Methods: The research included 105 AECOPD patients admitted to the Chest Diseases Division at Tishreen University Hospital in Lattakia from March 2019 to March 2020. Patients were sorted into two groups: elevated blood sugar (≥200 mg / dL) and non-elevated blood sugar (<200 mg / dL) with follow-up of patients’ clinical developments during hospitalization. Results: The death was more frequent in patients with high blood sugar (15.6% versus 3.3% in the other group) with a statistically significant difference (p-value = 0.02). The hospitalization period was longer with an average of (5.9±1.08) days versus (4±0.9) days in patients with non-hyperglycemia, with a statistically significant difference (p-value = 0.0001) and other complications such as hospital acquired pneumonia and the need for admission at intensive care unit were more frequent and statistically significant in the hyperglycemic group. The failure of non-invasive mechanical ventilation did not show a statistically significant difference between the two groups. Conclusion: Admission hyperglycaemia in AECOPD is an independent risk factor for both death, length of hospitalization, and other complications such as hospital acquired pneumonia and the need for admission at intensive care unit.